Zona hemisferica de libre comercio y los paises del Caribe = a hemispheric free trade zone and the Caribbean countries. - Griffith, Winston H. (1992)
Analyses the consequences that might result for the Caribbean countries in terms of costs and benefits of the establishment of a Hemispheric Free Trade Zone, taking into account not only the effects considered by the theory of integration, but also the historical experience of those countries.